Meningkatkan Kapasitas Kader Posyandu dalam Upaya Pencegahan dan Penanganan Stunting - Setyawati, Ari; Ariando Salomon, Glendy; Nordianiwati, Nordianiwati; Ayu Rahmadani, Risna; Herlina Herlina (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2023)
Stunting is a condition of growth failure in children; prevention has been attempted. One of the efforts is to form community empowerment cadres, namely posyandu cadres. Increasing the capacity of posyandu cadres is a strengthening of health education that can increase knowledge of the condition of individuals, families, and communities while maintaining healthy conditions and playing an active role in realizing optimal health status. This service activity aims to build the capacity of posyandu cadres to prevent and handle stunting. The results of service activities are an increasing understanding of toddler and pregnant women's nutrition seen from monitoring. The conclusion is that posyandu cadres can explain the importance of participating in posyandu activities every month, see the healthy development of toddlers and pregnant women using an interpersonal communication approach, and weigh and measure the baby's head circumference well. The filling of KMS has also been written correctly; this indicates an increase in the ability and skills of posyandu cadres.